UPLC-QTOF-MS/MS-guided isolation and purification of sulfur-containing derivatives from sulfur-fumigated edible herbs, a case study on ginseng. (25th April 2018) - Zhang, Li; Shen, Hong; Xu, Jun; Xu, Jin-Di; Li, Zhen-Ling; Wu, Jie; Zou, Ye-Ting; Liu, Li-Fang; Li, Song-Lin
Highlights: A UPLC-QTOF-MS/MS-guided preparation strategy for sulfur-containing derivative was proposed. Different roles of UPLC-QTOF-MS/MS analysis in the preparation were inducted. A new sulfur-containing derivative was efficiently prepared from sulfur-fumigated ginseng. Its chemical structure and generation mechanisms were elucidated and discussed. Abstract: In this study, a novel ultra-performance liquid chromatography coupled with quadrupole/time-of-flight mass spectrometry (UPLC-QTOF-MS/MS)-guidance strategy was proposed for preparation of sulfur-containing derivatives in sulfur-fumigated edible herbs. Being versatile in both chromatographic separation and mass spectrometric detection, UPLC-QTOF-MS/MS was inducted into each experimental step for multifaceted purposes including finding, tracking, purity determination and structural elucidation of targeted compounds as well as UPLC-HPLC chromatographic conditions transplantation, whereby the isolation and purification procedures were greatly facilitated. Using this strategy, a new sulfur-containing ginsenoside Rg1 derivative (named compound I) was obtained from sulfur-fumigated ginseng. The chemical structure of compound I was elucidated to be (3β, 6α, 12β)-3, 12-dihydroxydammar-25-ene-6, 20-diylbis-β-d -glucopyranoside, 24-sulfonic acid by QTOF-MS/MS, 1 H-NMR and 13 C-NMR analysis, and its generation mechanisms by sulfur-fumigation were accordingly discussed. The research deliverable suggests that the UPLC-QTOF-MS/MS-guidance strategy is promising for targeted preparation of sulfur-containing derivatives from sulfur-fumigated edible herbs.